Brood size manipulation showed little effect on baseline innate immune function in great tit (Parus major) nestlings and parents - Liu,Tiancheng (2023)
The trade-off between current and future reproduction is universal and forms the basis of life-history theory. Brood size manipulations is one of the most common way to test this trade-off. Although the effect of brood size manipulation on immune response have been tested in many studies, little is known about baseline innate immune function. To fill this gap, I created three groups (enlarged, reduced and control) by brood size manipulation. I used three types of immune assays, including bacteria killing assays (BKA), haemagglutination and haemolysis assays (HLHA) and haptoglobin assays, to get a diverse and extensive measurement on baseline innate immune function. My study aims to be an integrated exploration on the trade-offs between parental effort and immune function in parents and between growth rate and immune function in nestlings. My study has showed no clear evidence for a trade-off on baseline innate immunity caused by brood size manipulation. However, I found that both nestlings and adult males had higher lysis capability than females and a negative correlation between lysis and body mass. These results suggest a trade-off between the complement system and growth rate, as well as different life-history strategies by males and females in relation to immune system development.